ANALISIS PENINGKATAN KUALITAS PRODUK Y DENGAN PENDEKATAN METODE SIX SIGMA - Dwi Rizky Fitria; Dwi Djumhariyanto (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
To meet the market needs a manufacturing industry is required to continue to improve the quality of production through improvements in the production process. One way that can be used is the analysis of quality improvement with Six Sigma methods. This research aim to reduce the number of defects that can increase the value of sigma production. Based on the analysis results obtained sigma value of its current production of 3.42 with DPMO value 27429. The final result may boost the improvement recommendations sigma value to 3.50 and decrease the number of defects from 54.94 grams to 45.5 grams.